"Being on the wrong side of the digital divide": seeking technological interventions for education in Northeast Nigeria. Issue 6 (29th October 2020) - Martens, Marianne; Hajibayova, Lala; Campana, Kathleen; Rinnert, Gretchen Caldwell; Caniglia, Joanne; Bakori, Isa Garba; Kamiyama, Tsukuru; Mohammed, Liman Audu; Mupinga, Davison M.; Oh, Olivia Jeonghwa
Abstract : Purpose: This paper aims to report the initial findings of a project aiming to re-establish basic education in conflict-ravaged states in Northeastern Nigeria and to improve education providers' ability to plan and deliver basic educational services. The authors present a preliminary analysis of Nigerian teachers' access to information communication technology (ICT), their technology skills, as well associated national ICT policies. Design/methodology/approach: This case study uses results from two co-designed tools, administered using KoboToolbox to Education Managers in the first instance, and teachers in the second. The data from the tools form the basis for analysis. Findings: In the first instance, educational managers reported a lack of access to technology, the internet and to training and professional development. In the second instance, teachers reported issues present in the classroom environment, including poor infrastructure, a lack of resources and over-crowded classrooms. Very few teachers had access to computers or to the internet. Research limitations/implications: The 33 educational managers represent a small sample size and may not be fully representative of the region covered. The ICT Capacity Audit tool listed Excel in two different areas – basic Excel skills and using Excel for data analysis – which could have caused confusion for participants. The data collection should be repeated, expanded and compared for consistency. For the team, changes to the proposed (SENSE) box content meant that we were not able to deliver low-tech tools, such as Boogie Boards, or high-tech tools, such as tablets, to schools. Originality/value: Despite seemingly insurmountable challenges, the research team identified low-tech tools as a feasible resource in the classroom. Existing tools, such as teachers' smartphones and use of the WhatsApp application, can be used for sharing educational resources and providing teacher training. This paper argues that Nigeria needs up-to-date national ICT policies to guide in-country efforts to develop implementation of information technology initiatives for education.